PELATIHAN PENGGUNAAN EDINBURGH POSTNATAL DEPRESSION SCALE (EPDS) BAGI BIDAN DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI, PUSKESMAS LANGSAT DAN PUSKESMAS MELUR KOTA PEKANBARU TAHUN 2021 - LAILIYANA, LAILIYANA; SEPTI INDAH PERMATA SARI (KRIDA CENDEKIA, 2021)
It is estimated that around 50-70% of women giving birth show early symptoms of postpartum depression, although these symptoms can disappear slowly due to the process of adaptation and proper family support. Screening for psychological problems using the EPDS questionnaire in the context of early detection of depression in postpartum mothers is a solution that can be considered for health workers. However, in reality in the field, there are still many health workers, especially midwives who do not know about how to fill out the EPDS and its benefits. An overview of the results of community service activities that had previously been carried out in the form of socialization about EPDS to midwives, namely in 2016 at the Umban Sari Health Center, 2017 in the Rumbai Health Center Work Area, 2018 in the Rejosari Health Center Work Area and 2019 at the Sidomulyo Health Center and Sidomulyo Rawat Inap Health Center. there is an increase in the knowledge and skills of midwives in the use of EPDS as an early detection tool for postpartum depression between before and after socialization. This year’s Community Service activity is to provide training on the use of EPDS to midwives in the work area of ​​Payung Sekaki Health Center, Langsat Health Center and Melur Health Center. The purpose of this activity is to increase the knowledge and skills of midwives to be able to apply EPDS as a screening tool in early detection of psychological problems in postpartum mothers in midwifery services. The total number of participants was 57 Midwives. The method used is training and mentoring. Activities in the training are providing material and practice using the EPDS questionnaire. Assessment of knowledge and skills using a questionnaire containing questions about the use of EPDS as an early detection tool for postpartum depression. The results of the activity showed an increase in the average value of knowledge and skills of midwives, from 44.74 to 86.14. After training as many as 61.54% of midwives in the work area of ​​Payung Sekaki, Langsat and Melur Health Centers have implemented EPDS. It is recommended to the Head of the Puskesmas to be able to make an internal policy that regulates the use of EPDS by midwives as an early detection tool for Postpartum Depression as part of routine care in postpartum maternal services in the working area of ​​the Health Center.